Comparison of Qur'an Hadith Learning Results from TGT, Peer Tutoring, and STAD Models Based on School Background Factors - Muflihah, Muflihah; Fitriani, Fitriani; Rahayu Kariadinata; Malik, Adam; Rahmat, Yadi (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This research aims to compare the learning outcomes of Qur'an Hadith among three cooperative learning models, TGT, Peer Tutoring, and STAD, based on students' school backgrounds. This quantitative study used a comparative method to analyze data with SPSS 27 and the Two Way ANOVA test. The results revealed significant differences in Qur'an Hadith learning outcomes between students using the TGT model and those using Peer Tutoring, as well as between TGT and STAD (Sig.2-tailed < 0.05). However, there was no significant difference in learning outcomes between Peer Tutoring and STAD (Sig.2-tailed > 0.05). There was also no significant difference based on students' school backgrounds (SD, MI) (Sig. > 0.05). Furthermore, there was no interaction between the Learning Model and School Background in determining students' Qur'an Hadith learning outcomes (Sig. > 0.05). Overall, TGT proved to be the most effective teaching model in enhancing students' Qur'an Hadith learning outcomes, while students' school backgrounds did not influence these results.